PENERAPAN MODEL PEMBELAJARAN NOVICK UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN STOIKIOMETRI DI KELAS X MIA SMA NEGERI 1 PEKANBARU - Pratiwi, Wira; Azmi, Johni; Erviyenni, Erviyenni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research has been conducted at SMAN 1 Pekanbaru which aims to improve student learning achievement on the subject of ion stoichiometry in class X MIA. This type of research is an experimental study with a design Randomized Control Group pretest-posttest.. The sample from the study was students of class X MIA 1 as an experimental class. The experimental class is the class applied to the type Novick learning model. The data analysis technique used is the t-test. Based on the results of the data analysis test, t count> t table is 1,91> 1.67 meaning that the application of Novick learning model can improve student learning achievement on the subject stoichiometry in class X MIA SMA Negeri 1 Pekanbaru with categories of achievement improvement learning in the experimental class based on Score (N-Gain) is high, which is 0.81.Key Words: Probing-Prompting Learning, Learning Achievement, Stoichiometry